DISEÑO DE UN SISTEMA CONTABLE EN EL COMERCIAL LOOR DEL CANTÓN PIÑAS PROVINCIA DE EL ORO. EN EL PERIODO ENERO – JUNIO DEL 2015 - Aguilar Ruiz, Karla Yolanda (2015)
The thesis entitled "DESIGN OF AN ACCOUNTING SYSTEM IN THE COMMERCIAL LOOR OF PIÑAS CITY PROVINCE OF EL ORO. IN THE PERIOD JANUARY – JUNE 2015" was carried out with the aim of offering the owner of Commercial Loor quality information, and through the use of the multiple account system, determine in a systematic and effective way the current economic - financial business situation, for lead to the correct decision making. The development of the research contributed to the fulfillment of specific objectives, starting with to elaboration of accounting documents and necessary auxiliaries for the proper handling and register of the operations in the Commercial Loor. For the satisfaction of the second specific objective, a chart of accounts was elaborated with its correspondent manual adapted to business needs, in relation to the established in the international accounting norms, being used in the whole countable process. Then, the countable process takes place using the multiple account system, starting from the physical observation of assets, rights and obligations with the initial inventory, after this, the documentation source was systematized with the use of purchase auxiliaries, sales, fuels, 6 transport in purchases and charged bills; with this information the countable record of the operations was carried out in an ordered way, the daily book finished with the regulation of the account goods and the accounting adjustments, next the transactions were wholesale, and structure the balance of sums and residues. Applying as a countable tool the worksheet, the Financial States were prepared, with their respective explanatory notes and declarations to announce the owner the operational results of the period. In accordance with the obtained results, it was possible to determine that in the studied period a loss of $ exists 2.935,25, which principally is tied to deals that do not represent economic money payments; but, they correspond to not monetary adjustments carried out on having finished the economic period. In compliance to the last objective, the application and interpretation of financial indicators of liquidity are applied, indebtedness, activity and profitability, measuring the functioning of the organization in the researched period. The commercial Loor enjoys liquidity over the medium term, has $ 4.41 dollars to cancel for each dollar of owe, concentrates mainly on accounts receivable, the collection rate is 0.74 for which there is evidence that it needs a clear policy of debt collection that will increase the availability of cash. 7 It concluded with the conclusions presentation, among which stresses the importance of the application of an accounting system that allows the understanding of the real economic - financial situation in which the business is, due to it is suggested to the owner of Commercial Loor, adopt the accounting system designed and developed in this research work, with the purpose of having an indispensable tool for the management decision-making, that contributes to the growth and permanency in the business market.